2009
DOI: 10.5194/acp-9-6949-2009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling organic aerosols during MILAGRO: importance of biogenic secondary organic aerosols

Abstract: Abstract. The meso-scale chemistry-transport model CHIMERE is used to assess our understanding of major sources and formation processes leading to a fairly large amount of organic aerosols – OA, including primary OA (POA) and secondary OA (SOA) – observed in Mexico City during the MILAGRO field project (March 2006). Chemical analyses of submicron aerosols from aerosol mass spectrometers (AMS) indicate that organic particles found in the Mexico City basin contain a large fraction of oxygenated organic species (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
192
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(227 citation statements)
references
References 159 publications
(235 reference statements)
31
192
3
1
Order By: Relevance
“…During the high BB periods both datasets reported increases of modern carbon of about 15% of the total OC , which is consistent with the estimates from several other apportionment techniques as discussed above. A substantial fraction of non-fossil organic carbon (≥37%, ) is present during very low wildfire periods, which suggests the importance of urban sources of modern carbon such as food cooking or biofuel use (Hildemann et al, 1994;Mugica et al, 2009;Christian et al, 2010) and/or regional sources such as biogenic SOA (e.g., Stone et al, 2010a;Hodzic et al, 2009) and others. Hodzic et al (2010b) present the first comparison of modern carbon measurements with the predictions of a 3-D model, and find that the observed concentrations are similar to the measurements of Aiken et al (2010) but lower than those of Marley et al (2009a).…”
Section: T Molina Et Al: Mexico City Emissions and Their Transpomentioning
confidence: 99%
See 1 more Smart Citation
“…During the high BB periods both datasets reported increases of modern carbon of about 15% of the total OC , which is consistent with the estimates from several other apportionment techniques as discussed above. A substantial fraction of non-fossil organic carbon (≥37%, ) is present during very low wildfire periods, which suggests the importance of urban sources of modern carbon such as food cooking or biofuel use (Hildemann et al, 1994;Mugica et al, 2009;Christian et al, 2010) and/or regional sources such as biogenic SOA (e.g., Stone et al, 2010a;Hodzic et al, 2009) and others. Hodzic et al (2010b) present the first comparison of modern carbon measurements with the predictions of a 3-D model, and find that the observed concentrations are similar to the measurements of Aiken et al (2010) but lower than those of Marley et al (2009a).…”
Section: T Molina Et Al: Mexico City Emissions and Their Transpomentioning
confidence: 99%
“…The surface meteorological network, boundary layer measurements, and radar wind profiler measurements have also been used to examine the performance of meteorological predictions made by coupled meteorological-chemistryparticulate models, such as WRF-Chem Tie et al, 2009;Zhang et al, 2009a;Hodzic et al, 2009), to understand how forecast errors in meteorology affect predictions of trace gases and particulate matter. In general, the synoptic-scale circulations are simulated reasonably well by mesoscale models, although the details (i.e., timing and strength) of local and regional winds affected by terrain variations around Mexico City are more difficult to reproduce by models.…”
Section: Meteorological Modeling Studiesmentioning
confidence: 99%
“…Recently, Jaoui et al (2010) reported two new nitrogen-containing compounds (the structures are not identified) from isoprene oxidation under acidic conditions, which could be potentially served as tracers for isoprene SOA formation. In addition, highly time-resolved characterization of organic aerosol by using aerosol mass spectroscopy (AMS) (e.g., Hodzic et al, 2009) has been often reported in urban and rural sites as well as a continuous measurement of water-soluble organic carbon (WSOC) coupled to a particle-into-liquid sampler (PILS) (Miyazaki et al, 2006). These studies provide insights into the sources and processes that influence SOA production and their spatial and seasonal distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the study region, our calculations show that SOA contributes approximately 23.5 % to total OA. Our model SOA contribution is significantly lower than those reported for other remote locations (Jimenez et al, 2009) and this model issues will be explored in sensitivity calculations. There is an approximate balance between sources and sinks of BC and of OA.…”
Section: Geos-chem Model Budget and Model Comparison Against Measuremmentioning
confidence: 67%
“…By increasing the gas-particle partitioning coefficients of all SOA by a factor [%] of 100, we account for subsequent generations of oxidations that further lower their volatility. A similar factor was necessary to match model and observed organic aerosol over the Amazon basin (Hodzic et al, 2009). Table 8 shows that for this calculation we see the largest increases over tropical ecosystems, as expected, where the emissions of BVOCs and resulting production of SOA is largest.…”
Section: Sensitivity To Gas-phase Partitioning To Secondary Organic Amentioning
confidence: 99%